2013
DOI: 10.1016/s1470-2045(13)70158-x
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate endpoints for overall survival in chemotherapy and radiotherapy trials in operable and locally advanced lung cancer: a re-analysis of meta-analyses of individual patients' data

Abstract: SummaryBackgroundThe gold standard endpoint in clinical trials of chemotherapy and radiotherapy for lung cancer is overall survival. Although reliable and simple to measure, this endpoint takes years to observe. Surrogate endpoints that would enable earlier assessments of treatment effects would be useful. We assessed the correlations between potential surrogate endpoints and overall survival at individual and trial levels.MethodsWe analysed individual patients' data from 15 071 patients involved in 60 randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
136
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(142 citation statements)
references
References 27 publications
3
136
1
2
Order By: Relevance
“…The trial, therefore, once again stresses the well known difficulty of improving survival of patients with locally advanced NSCLC. The fact that a lack of benefit was seen both for survival and progression-free survival is consistent with a previous report that progression-free survival is a valid surrogate endpoint for overall survival in studies of chemotherapy and radiotherapy for patients with locally advanced lung cancers (7). As a positive finding, the PROCLAIM study demonstrated an acceptable safety profile of pemetrexed plus cisplatin.…”
supporting
confidence: 88%
“…The trial, therefore, once again stresses the well known difficulty of improving survival of patients with locally advanced NSCLC. The fact that a lack of benefit was seen both for survival and progression-free survival is consistent with a previous report that progression-free survival is a valid surrogate endpoint for overall survival in studies of chemotherapy and radiotherapy for patients with locally advanced lung cancers (7). As a positive finding, the PROCLAIM study demonstrated an acceptable safety profile of pemetrexed plus cisplatin.…”
supporting
confidence: 88%
“…STE is defined as the minimum treatment effect on the surrogate necessary to predict a non-zero effect on the true endpoint (47). It is normally presented as a Hazard Ratio (Table 3).…”
Section: Surrogate Threshold Effect (Ste)mentioning
confidence: 99%
“…The coefficient of determination (R 2 ) was calculated for analysis of correlations between the t p dependence of the results obtained with different methods. [28]. Statistical analysis was performed with SigmaPlot (12.0, Systat Software).…”
Section: Experimental Designmentioning
confidence: 99%